Microbiota dysbiosis influences immune system and muscle pathophysiology of dystrophin‐deficient mice. Issue 3 (19th December 2022) - Farini, Andrea; Tripodi, Luana; Villa, Chiara; Strati, Francesco; Facoetti, Amanda; Baselli, Guido; Troisi, Jacopo; Landolfi, Annamaria; Lonati, Caterina; Molinaro, Davide; Wintzinger, Michelle; Gatti, Stefano; et al.
Abstract: Duchenne muscular dystrophy (DMD) is a progressive severe muscle‐wasting disease caused by mutations in DMD, encoding dystrophin, that leads to loss of muscle function with cardiac/respiratory failure and premature death. Since dystrophic muscles are sensed by infiltrating inflammatory cells and gut microbial communities can cause immune dysregulation and metabolic syndrome, we sought to investigate whether intestinal bacteria support the muscle immune response in mdx dystrophic murine model. We highlighted a strong correlation between DMD disease features and the relative abundance of Prevotella . Furthermore, the absence of gut microbes through the generation of mdx germ‐free animal model, as well as modulation of the microbial community structure by antibiotic treatment, influenced muscle immunity and fibrosis. Intestinal colonization of mdx mice with eubiotic microbiota was sufficient to reduce inflammation and improve muscle pathology and function. This work identifies a potential role for the gut microbiota in the pathogenesis of DMD. Synopsis: The susceptibility of DMD patients to inflammatory events cannot solely be explained by skeletal muscle genetic defects but rather favors a new paradigm linking development of chronic inflammation with a strict regulation between epigenetics factors and degenerative environment. Gut microbiota–specific alterations (dysbiosis) correlate with the dystrophic pathology in mdx mice, influencing muscle immunity and fibrosis. Dysbiotic mdx microbiota induces a decreased innate immune response and altered muscle metabolism. The study of the dysregulated immune system‐microbiota axis in mdx mice highlights the importance of microbiota as a potential target for therapeutic interventions. Abstract : The susceptibility of DMD patients to inflammatory events cannot solely be explained by skeletal muscle genetic defects but rather favors a new paradigm linking the development of chronic inflammation with a strict regulation between epigenetics factors and degenerative environment.